If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x(x + -3) + x(-2x + -8) = 0 Reorder the terms: -1x(-3 + x) + x(-2x + -8) = 0 (-3 * -1x + x * -1x) + x(-2x + -8) = 0 (3x + -1x2) + x(-2x + -8) = 0 Reorder the terms: 3x + -1x2 + x(-8 + -2x) = 0 3x + -1x2 + (-8 * x + -2x * x) = 0 3x + -1x2 + (-8x + -2x2) = 0 Reorder the terms: 3x + -8x + -1x2 + -2x2 = 0 Combine like terms: 3x + -8x = -5x -5x + -1x2 + -2x2 = 0 Combine like terms: -1x2 + -2x2 = -3x2 -5x + -3x2 = 0 Solving -5x + -3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '-1x'. -1x(5 + 3x) = 0 Ignore the factor -1.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667Solution
x = {0, -1.666666667}
| x^3+15x^2+6x+1=0 | | 9x3/2 | | 9(2+t)-7(t+1)= | | Y=28x-2xsquared | | 5h+6(2h+10)=10 | | 3x-2(5x-y)-(4y+x)= | | w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 | | (2c)(3c)=6c | | 16340/40 | | 8*3=7x | | 15/2+4=-2 | | 36-45x+2=42x-49 | | k/3-19 | | (2x+30)=4x | | 11x-1=7x+10 | | -5(z+1)-(4z-6)=-10z | | 2n^2-n-120=0 | | 3x-8=158 | | 3(y-0.3)=19.4-y | | 2.4=t-/4.5 | | 6/3p-1=10 |